Integrated Role of Bifidobacterium animalis subsp. lactis Supplementation in Gut Microbiota, Immunity, and Metabolism of Infant Rhesus Monkeys - Xuan He (American Society for Microbiology, 2016)
ABSTRACT To investigate the impact of probiotic supplementation of infant formula on immune parameters, intestinal microbiota, and metabolism, five individually housed infant rhesus monkeys exclusively fed standard infant formula supplemented with probiotics (Bifidobacterium animalis subsp. lactis HN019) from birth until 3 months of age were compared with five standard formula-fed and five breast-fed monkeys. Anthropometric measurements, serum insulin, immune parameters, fecal microbiota, and metabolic profiles of serum, urine, and feces were evaluated. Consumption of B. lactis-supplemented formula reduced microbial diversity, restructured the fecal microbial community, and altered the fecal metabolome at the last two time points, in addition to increasing short-chain fatty acids in serum and urine. Circulating CCL22 was lower and threonine, branched-chain amino acids, urea, and allantoin, as well as dimethylglycine in serum and urine, were increased in the group supplemented with B. lactis compared with the standard formula-fed group. These results support a role of probiotics as effectors of gut microbial activity regulating amino acid utilization and nitrogen cycling. Future risk-benefit analyses are still needed to consolidate the existing knowledge on the long-term consequences of probiotic administration during infancy. IMPORTANCE Probiotics are becoming increasingly popular due to their perceived effects on health, despite a lack of mechanistic information on how they impart these benefits. Infant formula and complementary foods are common targets for supplementation with probiotics. However, different probiotic strains have different properties, and there is a lack of data on long-term health effects on the consumer. Given the increasing interest in supplementation with probiotics and the fact that the gastrointestinal tracts of infants are still immature, we sought to determine whether consumption of infant formula containing the probiotic Bifidobacterium animalis subsp. lactis HN019 for 3 months starting at birth would impact gut microbial colonization, as well as infant immunity and metabolism, when compared with consumption of formula alone.